Abnormality in Maternal Dietary Calcium Intake During Pregnancy and Lactation Promotes Body Weight Gain by Affecting the Gut Microbiota in Mouse Offspring. Issue 5 (3rd January 2019) - Li, Ping; Tang, Tiantian; Chang, Xuelian; Fan, Xiuqin; Chen, Xiaoyu; Wang, Rui; Fan, Chaonan; Qi, Kemin
Abstract : Scope: To investigate the effects of calcium status in early life on adult body weight and the underlying mechanisms involved in gut microbiota and related lipid metabolism. Methods and results: Three to four‐week‐old C57BL/6J female mice were fed diets with normal, insufficient, and excessive calcium respectively throughout pregnancy and lactation. The weaning male pups were fed with a high‐fat diet for 16 weeks, with a normal‐fat diet to the normal calcium group as control. The offspring fecal microbiota was analyzed by 16S rRNA high‐throughput sequencing, and mRNA expressions of genes were determined by the real‐time RT‐PCR. Maternal insufficient or excessive calcium intake exacerbated offspring obesity, with expressional changes in the Fasn, Acc1, LPL, Fiaf, and PPAR‐α genes in the liver or fat. The dysbiosis in gut microbiota in obese offspring was exacerbated by maternal imbalanced calcium intake, with increased Firmicutes and decreased Bacteroidetes in calcium insufficiency, and decreased Verrucomicrobia in calcium excess. Several genera, including Bacteroides, were reduced, and Lachnospiraceae and Lactobacillus were increased by maternal insufficient or excessive calcium intake. Conclusion: Imbalance in maternal calcium intake promotes body weight gain in offspring, which may be mediated by calcium's modulation on the gut microbiota and lipid metabolism. Abstract : Insufficient or excessive calcium intake during maternal pregnancy and lactation has a long‐lasting adverse effect on gut microbiota and lipid metabolism in mouse offspring, which may cause predisposition to obesity in later life.